Uma fronteira em integração: o papel da Paróquia de São Patrício de Itaqui na Fronteira Oeste da província do Rio Grande de São Pedro, na segunda metade do século XIX, 1850- 1870 - Rodrigues, Márcio Adriano de Lima (2012)
This dissertation integrates research line: Integration, Politics and Frontier, the MA in History of UFSM, and had the support of CAPES, through Stock Exchange DS. The objective focused on characterizing the commercial activity practiced in the Parish of St. Patrick Itaqui, located on the western border of the province of Rio Grande de São Pedro, Brazil, between 1850 and 1870. The commercial activity during this period involved a multitude of activities that have developed in local character, involving merchants, traders and moneylenders, who stood out in this border town, being identified from the records in the primary sources of legal and administrative character. Exploratory research and analytical documentary sources as the Common Shares Civil and Crime, Post-Mortem inventories, records of Notary Notary and Attorney Itaqui, found in the Public Archives of Porto Alegre, were added to the lists of Customs and Reports Mayor of Itaqui, located in the Historical Archive of Porto Alegre, to describe an activity marked by diversification of market practices and strategies implemented by merchants, traders and brokers in these spaces. It was observed that the large influx market, with the entrance of the harbor of St. Patrick Parish Itaqui, allowed the rise of characters like Manuel Marenco and Emigdio Bonorino, which began to take advantage of the opportunities afforded by maintaining links and ties political and economic elites in these spaces, to discuss plots of power at the local level. The capital that transited in free space would promote the promotion of commercial sectors in areas of wholesale and retail dry goods, practiced sales and shops, plus the actions of domestic and foreign businessmen linked to narrower markets involving credits, loans, land and cattle. Itaqui these contacts can enlarge spaces of economic exploitation allowing the performance of a number of agents in the expanded flows and local spaces